An up to 17‐year follow‐up retrospective analysis of a minimally invasive, flapless approach: 18 945 implants in 7783 patients. (15th February 2018) - Jesch, Philip; Jesch, Wolfgang; Bruckmoser, Emanuel; Krebs, Mischa; Kladek, Tibor; Seemann, Rudolf
Abstract: Background: This study investigates gender, age, jaw, implant position, loading protocol (immediate vs delayed), smoking, and type of surgery (punch vs flap) as influential factors of implant survival in a large patient collective. Purpose: To evaluate the survival rates of implants in patients using a mucoperiosteal punch for flapless implantation in the majority of cases in order to evaluate its medical efficacy and safety. Materials and Methods: Between 1994 and 2015 all patients with complete data treated at the Wienerberg Dental Clinic, Vienna, Austria, were included and statistically analyzed in Cox proportional hazard (PH) models. As patients with multiple implants were included, a clustering term was added to the Cox PH model to respect pooled failures in patients. Results: Of the initial 24 282 ANKYLOS/Dentsply implants placed in 8137 patients a total of 7783 patients with 18 945 implants were finally included. The mean follow‐up was 2.8 ± 3.2 up to 17.9 years. Cumulative survival rates (CSRs) after 1, 3, 5, and 10 years were 98.5%, 97.7%, 96.7%, and 93.0%, respectively. Of these, 17 517 (92.5%) implants were placed minimally invasive via a flapless approach by use of the ATP‐Punch with comparable survival rates as observed for flap surgery. The Cox PH models proved smoking (hazard ratio [HR] = 2.2) and implant position as significant factors of implant survival. In the maxilla, canines and third molars were identified as low risk sites in comparison to the most frequently implanted first premolar site. In the mandible, the central incisor and second premolar were identified as high‐risk sites, the canine as low risk site in comparison to the most frequently placed first molar site. Conclusion: The analyzed data concludes the safety and medical efficacy of the ATP‐Punch. The CSRs using this flapless technique are comparable to the classic surgical flap approach.